The potential of tannin from Sonneratia alba fruit in defaunation of rumen protozoa and reducing methane gas production: An approach to increase livestock digestive efficiency - Roni Pazla; Antonius Antonius; Zaitul Ikhlas; Anuraga Jayanegara; Laily Rinda Ardani; Maureen Chrisye Hadiatry; Jumjunidang Jumjunidang; Tri Budiyanti (Czech Journal of Animal Science)
This research explores the addition of mangrove (Sonneratia alba) fruit to reduce the production of methane and the total population of protozoa. The dosage for adding mangrove fruit is 0% (without addition), 1.5%, 3%, and 4.5% in sugarcane tops-based feed. Results include ruminal product fermentation, gas and methane emissions, total protozoa, microbial protein production, microbial biomass, and nutrient digestibility. The research findings showed that an additional 1.5% to 4.5% dose can reduce methane gas emissions and the total number of protozoa. The total number of protozoa at 4.5% (T3) reached 9.89 × 104 cells/ml and methane gas was 56.1 ml/g DM (dry matter); 8.41 ml/g OM (organic matter). This effect is attributed to the tannin content in mangrove fruit, which exhibits antimicrobial properties. However, increasing doses also reduced nutrient digestibility. The findings suggest that incorporating 1.5-4.5% mangrove (Sonnetaria alba) fruit as a source of tannins causes a positive impact which reduces protozoa populations and methane production without changing the ruminal fermentation product. However, the addition of mangrove fruit in this study caused also reduced nutrient digestibility.